Attitude and effectiveness of the use of technology-based learning among IIUM nursing students - Cho Cho Zaw, Cho Cho Zaw; Md Khair2, Nur Sera Azwa Binti (Global Academic Excellence, 2019)
Introduction: The changes of the education system that is taking place in Malaysia is driven by the advanced technology and communication devices that is available to students wherever they are either at campus or home. Hence, the implementation of technology-based learning (TBL) in institutions in Malaysia must be effectively delivered to students. The purpose of this study was to explore the attitude and effectiveness of using TBL among IIUM nursing students. Method/Materials: A quantitative, cross-sectional descriptive study was conducted among 307 IIUM nursing students. A well-structured questionnaire was developed to collect data. Statistical analysis of the data was carried out using SPSS and association between variables was analyzed using Chi-Square test. Result: Majority of the respondents (82.6%) have their own smartphone and laptop. There were 221 (80.1%) respondents almost always get access to a computer and among them, 219 (79.3%) almost always used it in learning. Relatively, there were 96% of the respondents showed positive attitudes toward the use of TBL. 87% of the respondents agreed that TBL is effective in their learning achievement. There is relationship between the attitude toward the use of technology and the effectiveness in learning among IIUM nursing students with p-value = 0.007. Conclusion: Technology indeed provides them a very good channel and platform in facilitating them searching information and getting knowledge. Future research is recommended to conduct a survey among the administrators, lecturers, and other related personnel.